A case report of confirmed difficult pulmonary tuberculosis based on the hybrid capture-based tNGS method - Weiqian Chen; Huimin Chen; Ze Liu; Xinle Chi; Yaomeng Chen; Huan Ye; Wenjie Huang; Chenlei Cao; Wei Weng (BMC Pulmonary Medicine)
Abstract Background Early diagnosis of pulmonary tuberculosis can greatly reduce the harm caused by the disease. However, traditional diagnostic methods have various shortcomings in diagnosing pulmonary tuberculosis. Currently, with the increasing popularity, iteration, and decreasing costs of Next-generation sequencing (NGS) testing technology, NGS is being more widely applied in the diagnosis of pulmonary tuberculosis. Case presentation A 29-year-old male presented with “fever accompanied by cough for more than 20 days.” Multiple chest CT scans revealed progressive enlargement of the right hilar lymph nodes and thickening of the interlobular septa in the right upper lobe. Routine testing of bronchoalveolar lavage fluid, search for tuberculosis bacilli, bacterial and fungal cultures, X-pert MTB/RIF, and multiplex PCR-based targeted Next-generation sequencing (mp-tNGS) results were all inconclusive. Finally, bronchoalveolar lavage fluid was sent for hybrid capture-based targeted Next-generation sequencing (hc-tNGS) testing, and special staining of the enlarged lymph nodes confirmed the diagnosis of pulmonary tuberculosis. Conclusion The hc-tNGS has significant value in diagnosing pulmonary tuberculosis, especially in cases that are difficult to detect with other methods. In the future, this could gradually become a routine diagnostic method for pulmonary tuberculosis, enhancing the accuracy of early diagnosis.